THE EFFECT OF EMPLOYEE ENGAGEMENT AND ORGANIZATION CULTURE ON COMPANY INNOVATION CAPABILITY - Mohamad Kohir Aman (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2019)
Innovation Capability is incredibly important for companies to survive and gain competitive advantages. Some researchers examined the influence of corporate culture on Innovation Capability and revealed that the culture of the adhocracy had a positive effect on the company's Innovation Capability (Ahmad, 1998; Barlow 1999). Besides, the ability of innovation was also influenced by how strong employee engagement in the company is (Gichohi, 2014). To see the influence of adhocracy organization culture and employee engagement towards innovation capability in Indonesia, research was conducted with State-Owned Enterprises (SOE) employees as the subjects, as their role in shifting the Indonesian economic sector. The research questionnaires were distributed to 300 SOE’s employees in some sectors with a rate of return of 69.3% or 208. Of the total questionnaires entered, 178 questionnaires were completed and could be processed. With 5% degree of accuracy and 95% significance level, the results of data processing showed that employee engagement has a positive effect on Innovation Capability proved to be significant with t count 6.942 at α = 0.001 while the research hypothesis of adhocracy culture had a positive effect on Innovation Capability was shown to be significant with t count 2.144 and α = 0.032.